Evaluación de la obtención del aceite esencial del eucalipto (eucalyptus) como plaguicida para el control de mosca blanca (aleyrodidae). - Pinto Flores, Erick Joel (2023)
This research had the objective of evaluating the obtaining of the essential oil of the eucalyptus (Eucaliptus) as a pesticide to control the whitefly. Therefore, an analysis of different combinations of eucalyptus oil with water was carried out; the methodology for the extraction of oil through the process of dragging by steam was established; where, 206 grams of eucalyptus leaves collected in the Atocha parish of the city of Ambato were used. The eucalyptus oil extraction was carried out in the laboratory of the Technical University of Cotopaxi, it was also an experimental and descriptive design, which favored the establishment of the study subject and the description of the behavior of the eucalyptus oil-based pesticide. The main results obtained were after the analysis of the essential oil of eucalyptus, which was mainly composed of 1.8 -Cineole (Eucalyptol), Alpha-Pinene, Limonene, Alpha-Terpineol and 2-Beta-Pinene, in addition to presenting a transparent liquid appearance. greenish and with a fresh minty aroma. Regarding the effectiveness of the oil as a pesticide, it was determined that the combinations of 0.45 ml of oil plus 2.55 ml of water, with 0.11 ml of Tween 80 emulsifier, which gives us a concentration of 15%, and 1.5 ml of oil plus 1.5 ml of water with 0.11 ml of Tween 80 emulsifier, which gives us a 50% concentration, eliminates a high number of whiteflies after a period of 2 and 6 minutes, respectively. It is concluded that the oil extracted from eucalyptus leaves can be used as an alternative pesticide to control whitefly, since it is a natural product that does not affect the plant, soil and environment.